2012
DOI: 10.1590/s0034-737x2012000600020
|View full text |Cite
|
Sign up to set email alerts
|

Levantamento de moscas-das-frutas e seus parasitoides em citros, no município de Viçosa, Minas Gerais

Abstract: Survey of fruit-flies and their parasitoids in citrus in Viçosa, Minas GeraisFruit flies are responsible for large losses in commercial orchards in Brazil, thus, it is important to know the predominant species in the region. The objective of this study was to study the occurrence of fruit flies (Diptera: Tephritoidae) and of their parasitoids in sweet orange (Citrus sinensis L. Osbeck), 'Poncã' mandarin (Citrus reticulate Blanco) and 'Rio' tangerine (Citrus deliciosa Ten), in Viçosa, Minas Gerais. The fruits w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…In these studies the prevalence of Anastrepha fraterculus (Wiedemann) and Anastrepha obliqua (Macquart) was observed, but no specimens of A. similis and A. aczeli were found. SOUZA et al (2012) also performed a survey in the northern State of Minas Gerais and found five species of Anastrepha, including A. zenildae, A. obliqua, A. sororcula, A. fraterculus and A. turpiniae in Viçosa, Minas Gerais, Brazil, a survey was carried out of species of fruit flies associated with citrus orchards, and the only species found was A. fraterculus (MACHADO et al, 2012).…”
Section: Palavras-chave: Citros Mosca-das-frutas Fruticultura Pragmentioning
confidence: 99%
“…In these studies the prevalence of Anastrepha fraterculus (Wiedemann) and Anastrepha obliqua (Macquart) was observed, but no specimens of A. similis and A. aczeli were found. SOUZA et al (2012) also performed a survey in the northern State of Minas Gerais and found five species of Anastrepha, including A. zenildae, A. obliqua, A. sororcula, A. fraterculus and A. turpiniae in Viçosa, Minas Gerais, Brazil, a survey was carried out of species of fruit flies associated with citrus orchards, and the only species found was A. fraterculus (MACHADO et al, 2012).…”
Section: Palavras-chave: Citros Mosca-das-frutas Fruticultura Pragmentioning
confidence: 99%